2012
DOI: 10.1143/apex.5.105801
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characterization of Charge Separation in WO$_{3}$–TiO$_{2}$ Nanoscale Heterojunction Investigated by the Transient Photovoltaic Technique

Abstract: The dynamic photo induced charge separation and transport properties of pulsed-magnetron-sputtered TiO 2 , WO 3 , and WO 3 -TiO 2 double-layer films were investigated using the transient photovoltage (TPV) technique. Effective charge separation and transport were observed for the WO 3 -TiO 2 heterojunction, which was about three times larger than those of the TiO 2 and WO 3 single-layer films. The TPV response of the WO 3 -TiO 2 heterojunction peaked at 28 ns with a recombination lifetime of 179 ns. These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…18,19 The TPV enhancement of CdS/TiO 2 film (2 CBDs) is not only due to the UV-light absorption of TiO 2 overlapping that of CdS QDs in 2 CBDs (as shown in Figure 2(a)) but mainly results from the photoexcited electrons injected from CdS into TiO 2 due to the CB of CdS QD above the CB edge of TiO 2 (as shown in Figure 3). 15 In the following process, the transient intensity decreases gradually with the increase of CdS CBDs from 2 to 14 CBDs (similar to Fig. 2(b)).…”
supporting
confidence: 75%
See 2 more Smart Citations
“…18,19 The TPV enhancement of CdS/TiO 2 film (2 CBDs) is not only due to the UV-light absorption of TiO 2 overlapping that of CdS QDs in 2 CBDs (as shown in Figure 2(a)) but mainly results from the photoexcited electrons injected from CdS into TiO 2 due to the CB of CdS QD above the CB edge of TiO 2 (as shown in Figure 3). 15 In the following process, the transient intensity decreases gradually with the increase of CdS CBDs from 2 to 14 CBDs (similar to Fig. 2(b)).…”
supporting
confidence: 75%
“…In contrast, a negative TPV signal denotes that the top electrode is negative with respect to the back electrode. 14,15 In this case, the positive transient signal indicates that photoexcited electrons transfer to the FTO substrate, and photoexcited holes remain in TiO 2 nanowires, due to the upward shift of conduction band-edge of n-type TiO 2 . 3 Note that the transient signal of the composite CdS/TiO 2 film of 2 CBDs occurs at a timescale of about 2.5 Â 10 À8 s, which is a little slower compared to TiO 2 nanowire array film.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Here, we discuss it in detail based on the band structure and work functions. It was reported that the work functions (F) of WO 3 lm, metallic Pt, and metallic Ag are 5.7 eV, [45][46][47] 5.65 eV, 48 and 4.26 eV, 49 respectively. In addition, the work function of the bimetallic alloy can be expressed by the sum of the work functions of the two metal components, 50 which means that the work function of the alloy lies at a level intermediate between monometallic Pt and Ag (4.26 eV < F Pt-Ag < 5.65 eV).…”
mentioning
confidence: 99%
“…The β factor enumerates the merit of field emission which strongly depends on several factors like emitter geometry, underlying substrate, conductivity, aspect ratio of nanostructure, inter electrode distance, spatial distribution of emitters etc. [12][13][14] The FN plot [ vs. ] (inset of Fig. 7a) exhibits a nice linear relationship in the high field region and suggests that the emission to be of F-N type.…”
Section: Field Emission Performancementioning
confidence: 99%